IRF8 is a Reliable Monoblast Marker for Acute Monocytic Leukemias. (24th October 2021) - Katz, Samuel G.; Edappallath, Susmitha; Xu, Mina L.
Abstract : Supplemental Digital Content is available in the text. Abstract : Blast evaluation in patients with acute monocytic leukemias (AMoL) is notoriously difficult due to the lack of reliable surface markers and cytologic subtleties on the aspirate smears. While blasts of most nonmonocytic acute leukemias express CD34, available immunohistochemical antibodies to monocytic blasts also mark normal background mature monocytes. We searched for a potential biomarker candidate by surveying specific gene expression profiles of monocyte progenitors. Our investigations led us to IRF8, which is a lineage-specific transcription factor critical for the production of monocytic and dendritic cell progenitors. In this study, we tested and validated a monoclonal antibody to IRF8 as a novel immunohistochemical stain for trephine core biopsies of human bone marrow. We assessed the expression of IRF8 in 90 cases of AMoL, including posttherapy staging bone marrows, 23 cases of chronic myelomonocytic leukemia, 26 cases of other acute myeloid leukemia subtypes, and 18 normal control marrows. In AMoL, there was high correlation of IRF8-positive cells to aspirate blast count ( R =0.95). Comparison of IRF8 staining to aspirate blast percentage in chronic myelomonocytic leukemia also showed good correlation ( R =0.86). In contrast, IRF8-positive cells did not correlate with blast count in other subtypes of acute myeloid leukemia ( R =0.56) and staining was <5% in all normal control marrows, even those with reactive monocytosis. We found that IRF8 was also weakly reactive in B cells and hematogones, with the latter accounting for rare cases of discrepancies. When IRF8 was used to categorize cases as AMoL, positive for residual leukemia or negative, the sensitivity was 98%, specificity was 82%, positive predictive value was 86%, and negative predictive value was 98%. These results demonstrate that IRF8 may serve as a clinically useful immunostain to diagnose and track AMoLs on bone marrow core biopsies. This can be particularly impactful in the setting of poor aspiration and focal blast increase. In the era of new targeted therapies that have been reported to induce monocytic outgrowths of leukemia, a marker for malignant monoblasts may prove even more critical.